Wernicke–Korsakoff syndrome associated with mtDNA disease. (July 2020) - Jimoh, Idris Janos; Sebe, Barbara; Balicza, Peter; Fedor, Mariann; Pataky, Ilona; Rudas, Gabor; Gal, Aniko; Inczedy-Farkas, Gabriella; Nemeth, Gyorgy; Molnar, Maria Judit
Introduction: Wernicke encephalopathy (WE) and Wernicke–Korsakoff syndrome (WKS) are well-known disorders caused by thiamine deficiency. In addition to the classical concept of these diseases, some literature data suggest a connection between mitochondrial dysfunction and WE/WKS. Psychotic disorders and WKS seem to run in families, as the deficiency of the oxidative phosphorylation can be a trigger factor in psychotic events and WE/WKS as well. We present a patient harbouring the m.A3243G mtDNA mutation with the clinical and magnetic resonance imaging (MRI) findings of WKS who developed schizophrenia with predominantly negative symptoms some years later. Case presentation: A 27-year-old woman was referred to our clinic with severe weight loss after severe vomiting episodes, memory dysfunction and gait ataxia. Family history, as well as clinical, imaging and laboratory findings suggested a mitochondrial aetiology of her symptoms. Brain MRI detected bilateral mild thalamic lesions and loss of corpus mammillae, indicating Wernicke encephalopathy. Genetic testing detected an m.A3243G mtDNA mutation, which has been frequently associated with mitochondrial encephalopathy with lactic acidosis and stroke-like episodes. High-dose vitamin B1 supplementation with supportive antioxidant therapy improved the patient's memory and learning disturbance; however, some months later she developed psychosis with predominantly negative symptoms and her cognitive functions deteriorated again. Both cognitive and negative symptoms responded well to cariprazine monotherapy. Discussion: Mitochondrial disease due to mtDNA alteration can be a rare cause of WE. In addition to vitamin B1 supplementation, cariprazine with significant dopamine D3 receptor binding can be useful to treat the predominantly negative symptoms and cognitive dysfunction in patients with mitochondrial dysfunction. Conclusion: We assume that patients with a mitochondrial disorder might be prone to develop WE/WKS and therefore need tailored supportive therapy during metabolic crisis as well as symptom-based personalized antipsychotic treatment.